Analisis Pengaruh Pertumbuhan Penjualan, Profitabilitas, Risiko Pasar, dan Inflasi Terhadap Nilai Perusahaan Sektor Consumer Non-Cyclicals - Pangestuti, Dewi; Said , Aldi Patria (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim: This study aims to identify the effect of sales growth, profitability, market risk, and inflation on firm value. Method: This quantitative research study utilized purposive sampling to obtain a sample of 59 companies. The data analysis technique used was the Generalized Method of Moments in Eviews 12. Research Finding: The study found that sales growth does not significantly influence firm value. However, profitability positively impacts firm value, while market risk and inflation have negative impacts. Theoretical contribution: This study enriches the literature on the relationship between sales growth variables, profitability, market risk, and inflation on company value, especially in the consumer non-cyclical sector, using the Generalized Method of Moments (GMM). Practitioner implication: This study provides insights for non-cyclical consumer sector companies in Indonesia to focus on resource management efficiency and cost control strategies to increase profitability. Research limitation: This analysis does not include other internal company factors, such as management policies or product innovations that can affect company value. Further research is needed to explore additional factors that can provide a more comprehensive understanding.